Pengaruh Kecemasan dan Mindset terhadap Hasil Asesmen Standardisasi Pendidikan Daerah (ASPD) Mata Pelajaran Matematika SMP - Yosica Nadilla Zahara; Kismiantini Kismiantini (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aimed to examine the relationships among mindset, anxiety, and the achievement of the Assessment of Regional Education Standardization (ASPD) results among ninth-grade students in public junior high schools in Yogyakarta City. Using a quantitative survey approach, the study involved 871 students selected through stratified random sampling based on the TPM stage 1 test scores from schools categorized into high, medium, and low strata for the 2022/2023 academic year. Data were collected using a questionnaire instrument, validated by two expert validators, and construct validity was confirmed through standardized loading factors, showing all items to be valid. Reliability was measured using Cronbach's Alpha, yielding 0.508 for mindset and 0.724 for anxiety. Data analysis employed Structural Equation Modelling (SEM) in R Studio, with model fit assessed through RMSEA, GFI, AGFI, and CFI criteria. Results revealed that the mindset measurement model demonstrated an excellent fit, and the anxiety measurement model also fit the data well after minor modifications. Structural model testing confirmed a good overall fit. Findings indicated that anxiety directly influenced ASPD achievement, with higher anxiety associated with lower results. Mindset did not have a direct effect on ASPD outcomes but negatively influenced anxiety, meaning a stronger growth mindset led to lower anxiety levels. Furthermore, mindset indirectly affected ASPD achievement through its impact on anxiety, demonstrating that fostering a growth mindset can enhance students’ performance by reducing anxiety.